Reliability of a standing isokinetic shoulder rotators strength test using a functional electromechanical dynamometer: effects of velocity - Martinez-Garcia,Dario; Rodriguez-Perea,Angela; Barboza,Paola; Ulloa-Díaz,David; Jerez-Mayorga,Daniel; Chirosa,Ignacio; Chirosa Ríos,Luis Javier (PeerJ, 2020)
Background The evaluation of the force in internal rotation (IR) and external rotation (ER) of the shoulder is commonly used to diagnose possible pathologies or disorders in the glenohumeral joint and to assess patient’s status and progression over time. Currently, there is new technology of multiple joint isokinetic dynamometry that allows to evaluate the strength in the human being. The main purpose of this study was to determine the absolute and relative reliability of concentric and eccentric internal and external shoulder rotators with a functional electromechanical dynamometer (FEMD). Methods Thirty-two male individuals (21.46 ±  2.1 years) were examined of concentric and eccentric strength of shoulder internal and external rotation with a FEMD at velocities of 0.3 m s−1 and 0.6 m s−1. Relative reliability was determined by intraclass correlation coefficients (ICC). Absolute reliability was quantified by standard error of measurement (SEM) and coefficient of variation (CV). Systematic differences across velocities testing circumstances, were analyzed with dependent t tests or repeated-measures analysis of variance in case of 2 or more than 2 conditions, respectively. Results Reliability was high to excellent for IR and ER on concentric and eccentric strength measurements, regardless of velocity used (ICC: 0.81–0.98, CV: 5.12–8.27% SEM: 4.06–15.04N). Concentric outcomes were more reliable than eccentric due to the possible familiarization of the population with the different stimuli. Conclusion All procedures examined showed high to excellent reliability for clinical use. However, a velocity of 0.60 m s−1 should be recommended for asymptomatic male patients because it demands less time for evaluation and patients find it more comfortable.
Keywords: Isokinetic; Shoulder; Strength; Velocity